A heart failure self-management program for patients of all literacy levels: A randomized, controlled trial [ISRCTN11535170] - Rothman Russell L; Corr Kelly E; Kosnar Margaret C; Bryant Mary E; Malone Robert M; DeWalt Darren A; Sueta Carla A; Pignone Michael P (BMC, 2006)
Abstract Background Self-management programs for patients with heart failure can reduce hospitalizations and mortality. However, no programs have analyzed their usefulness for patients with low literacy. We compared the efficacy of a heart failure self-management program designed for patients with low literacy versus usual care. Methods We performed a 12-month randomized controlled trial. From November 2001 to April 2003, we enrolled participants aged 30-80, who had heart failure and took furosemide. Intervention patients received education on self-care emphasizing daily weight measurement, diuretic dose self-adjustment, and symptom recognition and response. Picture-based educational materials, a digital scale, and scheduled telephone follow-up were provided to reinforce adherence. Control patients received a generic heart failure brochure and usual care. Primary outcomes were combined hospitalization or death, and heart failure-related quality of life. Results 123 patients (64 control, 59 intervention) participated; 41% had inadequate literacy. Patients in the intervention group had a lower rate of hospitalization or death (crude incidence rate ratio (IRR) = 0.69; CI 0.4, 1.2; adjusted IRR = 0.53; CI 0.32, 0.89). This difference was larger for patients with low literacy (IRR = 0.39; CI 0.16, 0.91) than for higher literacy (IRR = 0.56; CI 0.3, 1.04), but the interaction was not statistically significant. At 12 months, more patients in the intervention group reported monitoring weights daily (79% vs. 29%, p < 0.0001). After adjusting for baseline demographic and treatment differences, we found no difference in heart failure-related quality of life at 12 months (difference = -2; CI -5, +9). Conclusion A primary care-based heart failure self-management program designed for patients with low literacy reduces the risk of hospitalizations or death.